PENDAMPINGAN KPM UNTUK PENDATAAN STUNTING MENGGUNAKAN RUMUS MANUAL EXCEL - Mawardi, Faza Pradana; Tsuroya, Alihfa Hasna; Wardani, Dila Dwiva Kusumah; Nurulhasanah, Aisa; Fayza, Nabila; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Stunting is still a serious health problem in Indonesia, based on the 2018 Basic Health Research, the prevalence of stunted toddlers reached 30.8%. There are several factors that contribute to stunting, namely poor nutrition and consumption of unhealthy food, which have an impact on children's physical and cognitive growth. The Ciamis Regency Government targets reducing the stunting rate to 14% by 2024 through various programs such as stunting consultations and convergence services in villages. The main program is to assist Human Development Cadres (KPM) in collecting stunting data using manual Excel formulas as a solution to problems with the eHDW application. This activity involved FKIP Edu students as facilitators in 13 sub-districts to assist KPM in inputting stunting data accurately. The method used in delivering the material uses demonstration and discussion methods, where activities directly involve participants as data sources in mentoring activities. Evaluation shows that this program has succeeded in increasing data accuracy and active participation from KPM, village midwives and related parties, thus supporting efforts to accelerate stunting reduction in Ciamis Regency.